Triponderal mass index can be used as a potential tool to predict the risk of hyperuricemia in children and adolescents with obesity: a population-based study - Niu, Yang; Zhang, Yajie; Sheng, Jinye; Feng, Yi; Tang, Qingya; Shen, Xiuhua (Frontiers in Nutrition, 2025)
PurposeHyperuricemia (HUA), a common complication in children and adolescents with obesity, has not received sufficient attention. Therefore, the purpose of this study was to compare the predictive ability of different HUA obesity indicators.MethodsThe records of 349 children and adolescents with obesity aged 6–17 years (233 boys and 116 girls) who visited the Nutrition Clinic of Xinhua Hospital, Shanghai Jiao Tong University School of Medicine between January 2012 and December 2023 were included in this retrospective study. The relationship between different obesity indices and HUA was analyzed by univariate and multivariate analysis. The predictive value of triponderal mass index (TMI) and waist-to-height ratio (WHtR) for HUA was evaluated by the receiver operating characteristic (ROC) curve, and the optimal cutoff point was calculated.ResultsIn this study, the prevalence of HUA in the general population was 42.40% (41.20% in boys and 44.82% in girls). Multiple regression analysis revealed that after controlling for age and sex, body mass index (BMI), TMI, waist circumference (WC), hip circumference (HC), WHtR, fat mass (FM), and skeletal muscle mass (SMM) were independent risk factors for HUA (p < 0.05). After controlling for age and stratification by gender, BMI, WC, HC, and SMM of boys and girls with obesity were positively correlated with the risk of HUA (p < 0.05). However, TMI, WHtR, body fat percentage, and FM were only positively associated with the risk of HUA in obese girls (p < 0.05). Moreover, TMI and WHtR were 18.2 kg/m3 and 0.56, respectively, in the ROC curve analysis.ConclusionThe prevalence of HUA was high in children and adolescents with obesity aged 6–17 years. In addition, our results underscored that the combination of TMI and WHtR can be used as a potential early predictor of HUA risk in children and adolescents with obesity, especially in girls.